Pengaruh Keramahan Pegawai Dan Kesadaran Diri Terhadap Kualitas Pelayanan Pada Percetakan Serpico Bekasi Selatan - Hani Hardiyanti; Supriyanto; Dody Kurniawan (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study uses a quantitative type, with a population of 100 respondents. The sampling technique used is purposive sampling. Data collection was carried out using a questionnaire which was then processed using the SPPS version 26 analysis tool to determine the results of the hypothesis and measure the validity of the study. The results of the data obtained indicate that Employee Friendliness has a positive and significant effect on Service Quality, Self-Awareness has a positive and significant effect on Service Quality, Employee Friendliness and Self-Awareness have a positive and significant effect on Service Quality.